A Planned Behavior-Based Investigation of Knowledge Sharing in Construction Industry - Lee, Chia Kuang; Davidson, Elizabeth; Liu, Yao (2012)
Knowledge sharing has been widely believed one of the vital elements that propel an organization’s performance. However, the construction industry in Malaysia is currently suffering from the lack of knowledge sharing within organisations. Hence, this paper intends to investigate the key factors as well as their relationships that affect knowledge sharing in the industry. The theory of planned behaviour is adopted and a simplified model is proposed based upon. Data is collected by questionnaires. A series of statistical analysis reveals that employees’ intention to share knowledge within construction companies is affected more by their attitude and perceived behavioural control. Accordingly, it is suggested that organizations provide ground reasons why knowledge sharing is important and should be adopted as a daily practice.